Status kesehatan ginggiva pengguna alat ortodontik cekat pada mahasiswa Fakultas Kedokteran Universitas Udayana, Denpasar, Bali - Ni Made Yeni Septianing Diah; Putu Ika Anggaraeni; Louise Cinthia Hutomo (Intisari Sains Medis, 2019)
Background: Maintaining the cleanliness of the oral cavity in users of fixed orthodontic devices is a difficult thing to do, due to the form of a complicated fixed orthodontic device. Therefore this initial study aimed to determine the health status of university students of Faculty of Medicine, Udayana University, using fixed orthodontic devicesMethod: An observational cross-sectional study was conducted among 67 students using fixed orthodontic devices at the Medical Faculty of Udayana University. Several questions regarding the use of fixed orthodontic devices and oral examination using the Modified Gingival Index (MGI) were carried out. Descriptive data is displayed in percentage using SPSS version 25 software.Result: Of the 67 samples, the majority were female (79.1%), 21 years old (32.83%), more than 2 years used fixed orthodontic devices (41.8%), and had a control schedule on follow up (67,16%). The healthy status of gingiva with fixed orthodontic appliance users was found as many as 52 people (77.6%) and had ginggival health status on the mild inflammation criteria of 15 people (22.4%). The healthy status of gingiva with fixed orthodontic appliance users was found as many as 52 people (77.6%) and had ginggival health status on the mild inflammation criteria of 15 people (22.4%). Based on gingival status, it was found that more healthy criteria were found in women (59.70%), age 21 years (23.9%), use of orthodontic devices more than 2 years (31.34%), and regularity of controls (50.75%).Conclusion: Most of the students of the Medical Faculty of Udayana University as users of fixed orthodontic devices have good health status.